1995
DOI: 10.1051/lait:1995316
|View full text |Cite
|
Sign up to set email alerts
|

Extraction et analyse de la phase aqueuse de l'emmental à 4 stades d'affinage

Abstract: (Reçu le 17 janvier 1995 ; accepté le 22 février 1995)Résumé -Grâce à la mise au point d'un équipement prototype de pressage, une amélioration de la méthodologie d'extraction de la phase aqueuse des fromages proposée initialement par Barthel et al (1928a) a été réalisée. Les phases aqueuses d'emmental à 4 stades d'affinage: sortie saumure, entrée et sortie cave chaude, commercialisation, ont été extraites et caractérisées sur les plans bactériologi-que, physico-chimique et biochimique. La teneur en substance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0
10

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 14 publications
9
29
0
10
Order By: Relevance
“…It consisted of a collection vessel, a perforated vessel, an outer cover, and a heavy ram. The procedure of extraction was similar to Salvat-Brunaud et al [34] and Hassan et al [10]. Freshly grated cheese (800 g) was thoroughly mixed with 1000 g of washed sea sand and was placed in stainless steel mold lined with cheesecloth.…”
Section: Extraction Of Cheese Expressible Serummentioning
confidence: 99%
“…It consisted of a collection vessel, a perforated vessel, an outer cover, and a heavy ram. The procedure of extraction was similar to Salvat-Brunaud et al [34] and Hassan et al [10]. Freshly grated cheese (800 g) was thoroughly mixed with 1000 g of washed sea sand and was placed in stainless steel mold lined with cheesecloth.…”
Section: Extraction Of Cheese Expressible Serummentioning
confidence: 99%
“…Il est mélangé avec 2 volumes de sable de Fontainebleau, placé dans un tissu, dans le moule et pressé selon la technique décrite précédemment [41,43]. Les fractions jus et huile sont respectivement récupérées dans les parties inférieure et supérieure du liquide s'écoulant de la presse.…”
Section: Préparation Du Jus De Fromageunclassified
“…1) étaient comparables aux résultats déjà obtenus [41,43]. Les rendements (masse de jus/poids de fromage mis en oeuvre) étaient de 6,7, 4,8 et 6,3 % pour la phase aqueuse et de 7,6, 6,4 et 6,1 % pour la phase lipidique, respectivement pour les fromages A, B et C. Les extraits secs de la fraction aqueuse du jus filtré étaient de 142,24, 172,78 et 124,89 g .…”
Section: Obtention Du Jus De Fromageunclassified
“…The hydraulic press and the general conditions for its utilization, previously described by Salvat-Bmnaud et al [18], were used in our experiments. Cheese sampI es for pressing consisted of 6 pieces of cheese (total weight -1.2-1.6 kg) at each stage of ripening.…”
Section: Hydraulic Pressmentioning
confidence: 99%
“…Cheese sampI es for pressing consisted of 6 pieces of cheese (total weight -1.2-1.6 kg) at each stage of ripening. Cheese with rind and mould intact was first frozen (-20 "C), then grated while in a frozen state, and rapidly mixed with sand (150-250 um), An adjustment of the proportion of sand added to cheese was necessary, as the 2: 1 (w/w) sandlcheese ratio reported by other authors as suitable for cheeses with high total solids (TS) [1,13,17,18] was not suitable for soft cheese. Preliminary experiments, which varied the sand/cheese ratio and total solids of cheeses showed that the amount of sand had to be adjusted as a function ofTS in cheeses according to the following relation:…”
Section: Hydraulic Pressmentioning
confidence: 99%